Florida Solid and Hazardous Waste Regulation Handbook: State Regulation - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
This document contains a brief overview of the structure of state and local government, followed by a discussion of the major state laws regulating the management of solid and hazardous waste. In addition, it gives a breakdown of both applicable and other laws into major topic areas of interest. This is EDIS document FE454, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.